2006
DOI: 10.1016/j.comgeo.2005.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Partitions of complete geometric graphs into plane trees

Abstract: Consider the following question: does every complete geometric graph K 2n have a partition of its edge set into n plane spanning trees? We approach this problem from three directions. First, we study the case of convex geometric graphs. It is well known that the complete convex graph K 2n has a partition into n plane spanning trees. We characterise all such partitions. Second, we give a sufficient condition, which generalises the convex case, for a complete geometric graph to have a partition into plane spanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 12 publications
0
38
0
Order By: Relevance
“…It is often useful to restrict the subgraphs of G to a certain class or property. Among all subgraphs of K n , plane spanning trees, plane Hamiltonian cycles or paths, and plane perfect matchings, are of interest [1][2][3]8] i.e., one may look for the maximum number of these subgraphs that can be packed into K n .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is often useful to restrict the subgraphs of G to a certain class or property. Among all subgraphs of K n , plane spanning trees, plane Hamiltonian cycles or paths, and plane perfect matchings, are of interest [1][2][3]8] i.e., one may look for the maximum number of these subgraphs that can be packed into K n .…”
Section: Introductionmentioning
confidence: 99%
“…Bernhart and Kanien [5] give an affirmative answer for the problem when the points are in convex position. Bose et al [8] proved that every complete geometric graph K n can be partitioned into at most n − n 12 plane trees. Aichholzer et al [3] showed that Ω( √ n) plane spanning trees can be packed into K n .…”
Section: Introductionmentioning
confidence: 99%
“…Let us start right away with an illustrating example, which did indeed motivate our study. We came across the following intriguing open question, which was considered in [11] and investigated further in [6] and [24]: Given a complete geometric graph (edges as straight segments) on 2m points in general position in the plane, is it always possible to partition the edges into m crossing-free spanning trees? For addressing such problems, the concept of order types 1 is ubiquitously used in discrete and computational geometry, as it allows for classifying the infinite number of point sets of a given size into a finite number of equivalence classes, capturing combinatorial properties such as which pairs of spanned line segments cross and which points define the set's convex hull.…”
Section: Introductionmentioning
confidence: 99%
“…It is unknown whether for some constant ε > 0, every geometric drawing of K n has thickness at most (1 − ε)n; see [17]. Dillencourt et al [26] studied the geometric thickness of K n , and proved that 5…”
Section: Open Problemsmentioning
confidence: 99%